OBSTETRICAL EMERGENCIES AND THEIR OUTCOME IN A PERIPHERAL HOSPITAL IN KHYBER PUKHTOONKHUA - Ikram, Mobeen; Mahboob, Saira; Zainab, Sadia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the magnitude of various types of maternal emergencies and neonatal outcomes in order to ascertain the impact of maternal presentation on perinatal mortality in a peripheral hospital in Khyber Pakhtun Khwa Province.Study Design: Retrospective cross-sectional study.Place and Duration of Study: This study was carried out in the Department of Anesthesiology and Gynecology & Obstetric Department, Combined Military Hospital Thal, from Oct 2016 to Mar 2017.Methodology: Total 181 obstetric patients were included in the study. The patients’ documents were evaluated retrospectively for adverse maternal and neonatal outcomes, the incidence of various obstetrical emergencies, average time before proceeding with the emergency surgery and average duration of stay in our hospital.Results: The mean age of our study group was 27.1 ± 5.7 years. The mean time to operative delivery 57.0 ± 49.1 minutes. The mean length of hospital stay was 2.0 ± 0.50 days. Most of the patients presented at night (51.2%), without any antenatal visits (67.4%) with obstructed labour (24.8%). There were 30 (16.6%) perinatal deaths. Perinatal was correlated to obstructed labour, maternal hemorrhagic disorder, fetal distress and hypertensive disorder and presentation at night; p